(untitled) (LACCEI, 2024)
The term Agrovoltaic refers to the production of photovoltaic energy and the development of crops. This concept is of particular interest in regions of southern Peru where agriculture is one of the main drivers of the economy, and where solar radiation is ideal for the generation of photovoltaic energy. The objective of this research is to evaluate the impact on the cultivation of saladette tomatoes with adequate shading levels, adapted to the environmental conditions of arid and desert climates with high water needs. Four cultivation areas were established: one without photovoltaic panels as a control zone (area 1), and the others with different angles of solar panels with 20° (area 2), 30° (area 3), and 40° (area 4). As a result, the plants in the area 2 of the study showed greater vegetative development and higher production compared to the other study areas, contributing to minimizing the impact of stress caused by high solar radiation and high temperature, with water savings and improving the development of saladette tomato plants